ANALISA KERUSAKAN JALAN BETON PADA RUAS JALAN DESA BADURAME-GEGER KECAMATAN TURI - Hardi Susilo; Sugeng Dwi Hartantyo (Litbang Pemas - Universitas Islam Lamongan, 2017)
Badurame Village Street-Geger is a very important means of transportation. This is to support the economy of rural communities. The street is built by self-management way that has 3m wide and 2500m long. Badurame Village Street-Geger is an area that connects one settlement with the other settlements and one of the main accesses to the main road. Given the importance of transportation, the researcher conducted a research to determine the damage that occurred on the street. This study uses Bina Marga method, this method is used as a reference in the implementation, planning and solutions to the damage. From these results, the cause of the road damage on Badurame Village Street-Geger is the lack of reinforcement on the plate, aiming to minimize the lengthwise cracks because cracks is the most dominant reached 9.33% and reduced quality of concrete due to the lack of supervision. Amount of damage on the Badurame Village Street-Geger is the rift that extends reached 9.33%. Waning concrete is 0.08%, collapsed road is 0,093% and cracks crosways is 0.2%. Solutions to overcome damage on the Badurame Village Street-Geger using method or reference from Bina Marga is patching, resurfacing, filling, local reconstruction and overlay.